Емпатія як спосіб розуміння іншої людини: позитивні та негативні сторони - Узлова, А. Д. (ХНУРЕ, 2021)
Empathy is a social process by which a person understands and is aware of other people's emotions and behavior, and can often cause a person to feel the same emotions. With the proper development of the empathic process – there is an opportunity to help other people. Empathy plays a crucial role in human, social and psychological aspects at all stages of life. However, empathy motivates us to do things that may seem right now, but lead to tragic consequences in the future.
Keywords: філософія; емпатія